EU enlargement: Geopolitics meets integration policy. The EU is set to add gradualist elements to its enlargement doctrine - Barbara Lippert (Stiftung Wissenschaft und Politik (SWP), 2024)
Now that the European Council has given the green light to opening EU accession negotiations with Ukraine and Moldova, it is clear that the Union is no longer simply showing symbolic solidarity with neighbours invaded or threatened by Russia. Rather, a new chapter of enlargement policy is beginning in the shadow of war. After Turkey and the six Western Balkan countries, the third enlargement area is formed by Ukraine, Moldova and Georgia in Eastern Europe. Ever since Russia's full-scale invasion of Ukraine, Brussels has understood enlargement to mean expansion into strategically important regions. Geopolitical demands for rapid accession are gnawing away at the existing enlargement doctrine, according to which there can be neither compromises on the Copenhagen criteria for EU membership nor shortcuts along the path to accession. What is more, accession issues could soon enter the perilous waters of war diplomacy when lasting security for post-war Ukraine is at stake. In a bid to overcome the dilemma between geopolitics and integration policy, the European Commission is currently developing ideas about how new members can be integrated step by step.
Keywords: 320; European Council; European Commission; European Union; EU accession negotiations; Ukraine; Moldova; Georgia; Bosnia-Herzegovina; Russia